Impact of Electronic commerce In Imposition of taxes - عبد, سهاد كشكول (Journal of Economics and Administrative Sciences, 2012)
That the possibility of imposing a tax on electronic commerce is increasing interest in it by governments in developed and developing countries alike, and there is interest in a logical by governments and bodies of taxation, in particular in developing countries erosion potential tax in the tax base resulting from the adoption of e-commerce if not mutation rules and tax legislation, local and international to take into account this important economic developments and how to keep up, said the combination of the taxation system is the only way to increase revenue needed to finance government spending on goods and services needed by society.The most important conclusions reached by the research's lack of financial structure and cash appropriate to facilitate the payments and adjustments resulting from the transactions in electronic commerce, where you must develop the financial services and strengthen the credit system and uphold standards of financial transfers where the conduct of settlement of accounts and payments arising from electronic commerce. Lack Career tax capable of dealing with electronic commerce and applications of modern technology in the absence of technical graduates working in this area of ​​the hand, and not to develop capabilities of staff in the tax on the other hand through their involvement in training courses in this area. And recommended research to the development of tax legislation in line with technical developments taking place in the world of electronic commerce and the Internet. And work on rehabilitation of infrastructure and services tax withhold and connected to the Internet to prevent "double taxation for domestic and global